A Study on Pseudo Symmetric ðšª-Ideals in Ternary ðšª-Semigroups - Vasantha, M; Madhusudhana Rao, D; Satish, T; Kumar, Srinivasa (International Journal of Engineering and Technology, 2018)
In this paper section 1 reflects, the terms, â€˜PSTðšª-idealsâ€™ of a ternary Î“-semigroup and â€˜PSTðšª-semi groupâ€™ are introduced can characterized PSTðšª-semi group. In section 2, the terms, â€˜SPSTðšª-ideals, â€˜SPSTðšª-semi groupâ€™ are introduced and classified these Â SPSTðšª-ideals.Â